Comparison of a resorbable magnesium implant in small and large growing-animal models. (15th September 2018) - Grün, N.G.; Holweg, P.; Tangl, S.; Eichler, J.; Berger, L.; van den Beucken, J.J.J.P.; Löffler, J.F.; Klestil, T.; Weinberg, A.M.
Graphical abstract: Abstract: Fracture treatment in children needs new implant materials to overcome disadvantages associated with removal surgery. Magnesium-based implants constitute a biocompatible and bioresorbable alternative. In adults and especially in children, implant safety needs to be evaluated. In children the bone turnover rate is higher and implant material might influence growth capacity, and the long-term effect of accumulated particles or ions is more critical due to the host's prolonged post-surgery lifespan. In this study we aimed to investigate the degradation behavior of ZX00 (Mg-0.45Zn-0.45Ca; in wt.%) in a small and a large animal model to find out whether there is a difference between the two models (i) in degradation rate and (ii) in bone formation and in-growth. Our results 6, 12 and 24 weeks after ZX00 implantation showed no negative effects on bone formation and in-growth, and no adverse effects such as fibrotic or sclerotic encapsulation. The degradation rate did not significantly differ between the two growing-animal models, and both showed slow and homogeneous degradation performance. Our conclusion is that small animal models may be sufficient to investigate degradation rates and provide preliminary evidence on bone formation and in-growth of implant materials in a growing-animal model. Statement of Significance: The safety of implant material is of the utmost importance, especially in children, who have enhanced bone turnover, more growth capacity and longer postoperative lifespans. Magnesium (Mg)-based implants have long been of great interest in pediatric orthopedic and trauma surgery, due to their good biocompatibility, biodegradability and biomechanics. In the study documented in this manuscript we investigated Mg–Zn–Ca implant material without rare-earth elements, and compared its outcome in a small and a large growing-animal model. In both models we observed bone formation and in-growth which featured no adverse effects such as fibrotic or sclerotic encapsulation, and slow homogeneous degradation performance of the Mg-based implant material.